Control Efficiency of Persistence of Biotronics Networks - Balaišis, P.; Keras, E.; Valinevičius, A. (Elektronika ir Elektrotechnika, 2008)
It is indicated, that when expanding over territories the systems of control of interfaces of biological and electronic objects – biotronics systems, their networks are created and problems of efficiency assurance of information transmission using these networks emerge. It is stated that improvement of network persistence is one of the measures for increasing this efficiency. Persistence control scheme of network of biotronics systems is presented and formulas are offered for calculation of probability of information transmission task accomplishment. Method of determination of network persistence level is presented. Stochastic nature of persistence of biotronics systems networks is emphasized. Method for forecasting of network redundancy losses is offered. Persistence control possibilities of the network of systems are investigated. Ill. 2, bibl. 6 (in English; summaries in English, Russian and Lithuanian).